31.0k views
1 vote
Which expression is NOT equivalent to the other three?

A) 2x − 2.5 + 3x − 3
B) 5(x − 1.1)
C) 5(x − 5.5)
D) 5x − 5.5

2 Answers

2 votes

Answer:

C

Explanation:

A: You can combine like terms. 2x + 3x = 5x. 2.5 + 3 = 5.5 A = 5x - 5.5

B: You can use distributive property. 5x - 5.5

C: If you use the distributive property you get 5x + 27.

D: D is 5x - 5.5

So the only one that does not equal 5x - 5.5 is C.

Hope this helps :)

User Jasonkim
by
5.4k points
4 votes

Answer:

c)

Explanation:

A) 2x − 2.5 + 3x − 3 = 5x - 5.5

B)5(x-1.1) = 5x - 5*1.1= 5x - 5.5

D)5x - 5.5

But C) is not equivalent

5(x-5.5) = 5x - 5*5.5 = 5x - 27.5

User Sebastian Zartner
by
4.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.